Peraturan Daerah Nomor 1 Tahun 2015 Tentang Rencana Tata Ruang Wilayah Kota Depok Tahun 2012–2032 (Analisa Pembangunan Ruang Terbuka Hijau (RTH) Hutan Kota Universitas Indonesia) - Sidqi, Mochammad Affani; Aminudin, Cecep (HUMANIORUM, 2025)
The management of Green Open Space (RTH) in the Universitas Indonesia (UI) urban forest area is crucial for maintaining environmental quality and the balance of urban ecosystems, as regulated in Regional Regulation Number 1 of 2015 on the Spatial Planning of Depok City for 2012–2032. This study uses a juridical- empirical method to analyze the extent to which the implementation of regulations related to RTH complies with the provisions in the regional regulation. Based on regulatory analysis and field observations, despite the clear legal foundation provided by the regulation, its implementation still faces challenges such as land- use changes, weak coordination between institutions, and a lack of public awareness regarding the importance of preserving RTH. Oversight of the regulation’s implementation is also weak, leading to discrepancies between plans and actual outcomes. Therefore, improving supervision, enforcing stricter laws, and fostering collaboration between the government, Universitas Indonesia, and the community are essential to ensure that the management of RTH in the UI urban forest aligns with sustainable spatial planning principles.